Depressive symptoms in higher education students during the COVID-19 pandemic: the role of containment measures. (15th March 2022) - Buffel, Veerle; Van de Velde, Sarah; Akvardar, Yildiz; Bask, Miia; Brault, Marie-Christine; Busse, Heide; Chatzittofis, Andreas; Ladner, Joel; Rabiee-Khan, Fatemeh; Stathopoulou, Theoni; Tavolacci, Marie-Pierre; van der Heijde, Claudia; et al.
Abstract: Background: Students are a vulnerable group for the indirect impact of the COVID-19 pandemic, particularly their mental health. This paper examined the cross-national variation in students' depressive symptoms and whether this can be related to the various protective measures implemented in response to the initial stage of the COVID-19 outbreak. Methods: Student data stem from the COVID-19 International Student Well-being Study, covering 26 countries during the first wave of the COVID-19 pandemic. Country-level data on government responses to the COVID-19 pandemic were retrieved from the Oxford COVID-19 Tracker. Multilevel analyses were performed to estimate the impact of the containment and economic support measures on students' depressive symptoms ( n  =   78 312). Results: School and workplace closures, and stay-at-home restrictions were positively related to students' depressive symptoms during the COVID-19 pandemic, while none of the economic support measures significantly related to depressive symptoms. Countries' scores on the index of these containment measures explained 1.5% of the cross-national variation in students' depressive symptoms (5.3%). This containment index's effect was stable, even when controlling for the economic support index, students' characteristics, and countries' epidemiological context and economic conditions. Conclusions: Our findings raise concerns about the potential adverse effects of existing containment measures (especially the closure of schools and workplaces and stay-at-home restrictions) on students' mental health.